IMPLEMENTASI PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) TERINTEGRASI KONSEP UNDERSTANDING BY DESIGN (UBD) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI KELAS V SDN KARANGREJO 4 - Nahdiah Nur Fauziah; Wildatul Ummah; Miftakhul Khoir; Toha Nantra; ST. Mislikhah; Sofyan Hadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the implementation of the Teaching at the Right Level (TaRL) approach integrated with the Understanding by Design (UbD) framework to improve the mathematics learning outcomes of fifth-grade students at SDN Karangrejo 4. The problem stems from the imbalance in numeracy skills and low understanding of number operations concepts due to classical learning that has not been adjusted to students' learning readiness. This study aims to describe the planning, implementation, assessment process, and student responses to the TaRL-UbD model, as well as to analyze its contribution to improving learning outcomes. Using a qualitative descriptive approach, data were collected through classroom observations, in-depth interviews, and documentation involving teachers, students, and the principal. The results show that diagnostic assessments successfully map students into three levels of basic, intermediate, and advanced abilities, which form the basis for differentiated learning. The integration of UbD ensures clear learning objectives and aligned assessments, while TaRL provides targeted interventions according to students' mastery levels. The findings show an increase in procedural accuracy, understanding of number operations, learning engagement, and student confidence. Teachers also reported more focused classes and more meaningful learning interactions. Overall, the TaRL–UbD model has proven effective in creating adaptive and focused mathematics learning, making it a promising strategy for strengthening numeracy in elementary schools.